THE SYSTEM FOR ASSESSING THE CREATIVE ACTIVITY OF FUTURE PRIMARY SCHOOL TEACHERS AND ITS EFFECTIVENESS (International Educators Conference, 2025)
This article studies the issues of developing the creative activity of future primary school teachers and improving the system for assessing it. The study analyzes the content of creative activity, the role of the teacher in the professional formation of the teacher, and the impact of assessment criteria on the educational process. Also, existing assessment systems are analyzed and their effectiveness is compared on the basis of experimental work. It is shown that the assessment model developed based on an innovative approach has yielded positive results in developing the creative competencies of future teachers. The article also highlights the pedagogical and psychological factors that are important in the development of creative activity, and also gives practical recommendations for improving the system.